(Dis)honesty and the Value of Transparency for Campaign Promises - Matthias Lang; Simeon Schudy (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2023)
Promise competition is prevalent in many economic environments, but promise keeping is often difficult to observe. We study the value of transparency for promise competition and ask whether promises still offer an opportunity to honor future obligations when outcomes do not allow for observing promise keeping. Focusing on campaign promises, we show theoretically how preferences for truth-telling shape promise competition when promise keeping can(not) be observed and identify the causal effects of transparency in an incentivized experiment. Transparency leads to less promise breaking but also to less generous promises. Rent appropriations are higher in opaque institutions though only weakly so when not fully opaque. Instrumental reputational concerns and preferences for truth-telling explain these results.
Keywords: C91; C92; D72; D73; D91; 330; campaign promises; promise breaking; voting; lying costs; preferences for truth-telling; political Economy; theory; experiment